Validation of Orchids and Sunflowers program, a proposed of work in children's mental health - Bustamante Soto, María Elsa (2000)
This article shows the results obtained starring from the study that REDINFA carried out to validate a work proposal in infantile mental health. The program "Orchids and Sunflowers» it is a program that he/she responds to two basic objectives that it is the one of to support children affected by the political violence and to favor their development psychosocial. The present validation was carried out with children from 7 to 14 years of age. The program works under three fundamental axes that are the person; the family and the community. As for the person it is looked for that the children recognize Their abilities and dexterities and in turn Their defects and virtues stop this way to overcome difficult situations and lo look with optimism the future. As for family; it is the that they recognize their family history and to be able to understand the because of the estrangement of their origin community and finally as for community; it is the one of revaluing their customs and habits of life of their previous residence place; and that in the current space They can be given bill that they are able to influence in their development. The program begins with a first moment to lake contact with the population objective and through Playful activities to develop nexuses of trust and this way to begin the program that consisted or 25 sessions in those that you work three axes: That valuable I am. it is This way my family and living in community. The validation is carried out by means of the application or a record or indicators that you/they have 6 areas that are: Relate Interpersonal; expression or thoughts and feelings. personal valuation. identify. Of these it was found that of identity had better results: not being this way with those of personal valuation and that of interpersonal relationships.